Pengaruh Budaya Kerja Dan Kompensasi Terhadap Kinerja Karyawan Di Baznas Provinsi Kalimantan Timur - Rismawati, Rismawati; Mainata, Dedy; Rahmatullah, Nur (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The human resources within an institution play an important role in determining its success. To improve employee performance, namely by providing work culture and compensation. With a good work culture and compensation, employee performance will also increase. By implementing work culture and compensation, HR will improve performance for the goals to be achieved. This research aims to determine the influence of work culture and compensation on performance at Baznas East Kalimantan Province. This type of research is quantitative research. The method used is causal associative. Making employees who work at Baznas East Kalimantan Province the population in this research with a total of 18 people. The sampling technique uses a saturated sample technique, where the total population is 18 people. The data sources in this research were obtained from primary data from questionnaires and secondary data in the form of journals, other literature and sources related to the problems studied. Data collection was carried out using questionnaires and literature studies and using a Likert Scale as the measurement scale. Data analysis techniques include research instrument testing (validity test, reliability test), classic assumption test consisting of (normality test, multicollinearity test, heteroscedasticity test and linearity test) multiple regression analysis test, hypothesis testing consisting of (t test, f test ) and coefficient of determination test (R²). Based on the research results, it is known that the work culture variable has a significant effect on employee performance. Meanwhile, the Compensation variable has no significant effect on Employee Performance. The percentage of influence exerted by the Work Culture (X1) Compensation (X2) Employee Performance (Y) is 35.5% while the remaining 65.5% is influenced by other factors not included in this research.